Potential therapeutic targets of macrophages in inhibiting immune damage and fibrotic processes in musculoskeletal diseases - Zhu, Jianshu; Fan, Jiawei; Xia, Yuanliang; Wang, Hengyi; Li, Yuehong; Feng, Zijia; Fu, Changfeng (Frontiers in Immunology, 2023)
Macrophages are a heterogeneous cell type with high plasticity, exhibiting unique activation characteristics that modulate the progression and resolution of diseases, serving as a key mediator in maintaining tissue homeostasis. Macrophages display a variety of activation states in response to stimuli in the local environment, with their subpopulations and biological functions being dependent on the local microenvironment. Resident tissue macrophages exhibit distinct transcriptional profiles and functions, all of which are essential for maintaining internal homeostasis. Dysfunctional macrophage subpopulations, or an imbalance in the M1/M2 subpopulation ratio, contribute to the pathogenesis of diseases. In skeletal muscle disorders, immune and inflammatory damage, as well as fibrosis induced by macrophages, are prominent pathological features. Therefore, targeting macrophages is of great significance for maintaining tissue homeostasis and treating skeletal muscle disorders. In this review, we discuss the receptor-ligand interactions regulating macrophages and identify potential targets for inhibiting collateral damage and fibrosis in skeletal muscle disorders. Furthermore, we explore strategies for modulating macrophages to maintain tissue homeostasis.